Effectiveness of using post operative drain support system post parotid and thyroid surgery in Hospital Sains Malaysia - A/L Appannan, Vengatesh Rao (2018)
Background: Surgical drains can be very troublesome as they can pose problems in post-operative patients. This study was done to determine the effectiveness of Redivest to facilitate drain care in post-operative patients. Objectives: To assess the effectiveness of using the Redivest in reducing the pain score at the drain site, increasing comfort level and reducing complication of having a drain post parotid and thyroid surgery Methods: This is an interventional study, conducted on 39 patients, who underwent parotid and thyroid surgery and had drains inserted in Hospital Universiti Sains Malaysia from July 2016 to July 2017 involving 39 patients who were randomized into 2 groups with the post-operative drain support system termed as “Redivest”, and the other was the control group where drains were anchored via the conventional method. Patients were given a questionnaire, which comprises of a yes or no answer and Likert scale best suited to their impression to answer during the hospital stay. Results: 39 patients participated in this study aged from 18 to 80 from the Malaysian community comprising of the Malay and non-Malay ethnic group. Results showed difference in pain score observed between the two groups. The median pain score in in Redivest group was pain score of 1 while the median pain score on the control group was 2. Based on the Mann-Whitney U Test, the p-value is significant p-value < 0.001. The median comfort score in Redivest group was 19.00 while the median comfort score on the control group was 9.50. Based on the Mann- Whitney U Test, the p-value < 0.001 is significant. There were no complications seen in the Redivest group and the control group therefore could not be analyzed Conclusion: Usage of Redivest significantly improves the comfort and pain at the drain site, however the reduction in infections were insignificant.